1994
DOI: 10.1161/01.cir.89.5.2283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ischemic preconditioning on interstitial purine metabolite and lactate accumulation during myocardial ischemia.

Abstract: The purpose of this study was to determine the effect of ischemic preconditioning on the changes in interstitial fluid (ISF) purine metabolites and lactate during prolonged regional myocardial ischemia. The study consisted of two groups of anesthetized dogs: a control group (n = 13) that was exposed to 60 minutes of regional myocardial ischemia and a preconditioned group (n = 10). In the preconditioned group, regional myocardial ischemia was induced for two 5-minute episodes, each followed by 10 minutes of rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
4

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(58 citation statements)
references
References 35 publications
4
49
4
Order By: Relevance
“…9 In contrast, there is a report indicating that increases in adenosine concentration in the interstitial space are not augmented during sustained ischemia in the ischemic preconditioning group. 109 We also observed the differences between the interstitial and the coronary venous adenosine levels during sustained ischemia in the ischemic preconditioning group in our experiments. One possible explanation for this difference is that we measured adenosine concentration in coronary venous blood, and the adenosine level in the coronary venous blood is largely affected by endothelial cells.…”
Section: Preconditioning and Ecto-5'-nucleotidasesupporting
confidence: 67%
See 2 more Smart Citations
“…9 In contrast, there is a report indicating that increases in adenosine concentration in the interstitial space are not augmented during sustained ischemia in the ischemic preconditioning group. 109 We also observed the differences between the interstitial and the coronary venous adenosine levels during sustained ischemia in the ischemic preconditioning group in our experiments. One possible explanation for this difference is that we measured adenosine concentration in coronary venous blood, and the adenosine level in the coronary venous blood is largely affected by endothelial cells.…”
Section: Preconditioning and Ecto-5'-nucleotidasesupporting
confidence: 67%
“…In any of these possible situations, the temporal and topical increases in the adenosine concentration surrounding ecto-5'-nucleotidase may be able to directly activate the adenosine receptors located at the same cellular membrane, which may not contradict Van Wylen's observation. 109 This close juxtaposition may explain how ecto-5'-nucleotidase activates the adenosine receptors. Indeed, the regulatory systems, including the ATP receptors, G proteins, ecto-5'-nucleotidase and KATP channels, are closely linked with each other and are present in a single patch of no more than 1 mm 2 .…”
Section: Preconditioning and Ecto-5'-nucleotidasementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, successively lower peak levels of adenosine were observed following each ischemia/reperfusion cycle. These findings were also observed by others (146)(147)(148)(149). It was suggested that the die away curve pattern of adenosine was due to diminished nucleotide decay induced by IP (146).…”
Section: Our Experimental Findingssupporting
confidence: 79%
“…This controversy also arises in large part from the fact that if ecto-5Ј-nucleotidase played a major role in mediating preconditioning, one would expect it to cause an elevation of adenosine levels in myocardial tissue, whereas an opposite pattern (ie, a decrease in tissue adenosine) has been reported during classic ischemic preconditioning, 20 as well as after pharmacological preconditioning with isoflurane 21 or potassium channel openers. 22 In turn, one could argue that because of the predominantly endothelial location of ecto-5Ј-nucleotidase, 18,20 endothelium-derived adenosine may be preferentially released into the vascular compartment and thus escape interstitial fluid sampling with microdialysis techniques (indeed, a reduction in ischemic changes occurring with repeated balloon occlusions during angioplasty procedures correlates with an increased release of adenosine in the coronary venous effluent). 23 Together, these considerations suggest that it is important to make a clear distinction between ecto-5Ј-nucleotidase, taken as a surrogate marker of PKC activation, which sounds acceptable, and ecto-5Ј-nucleotidase, taken as an intrinsically cardioprotective compound mediating the preconditioning response, which remains more uncertain.…”
Section: Discussionmentioning
confidence: 99%